Developing Your Career in an Age of Team Science. (1st June 2012) - Zucker, Deborah
Abstract : Academic institutions and researchers are becoming increasingly involved in translational research to spur innovation in addressing many complex biomedical and societal problems and in response to the focus of the National Institutes of Health and other funders. One approach to translational research is to develop interdisciplinary research teams. By bringing together collaborators with diverse research backgrounds and perspectives, these teams seek to blend their science and the workings of the scientists to push beyond the limits of current research. While team science promises individual and team benefits in creating and implementing innovations, its increased complexity poses challenges. In particular, because academic career advancement commonly focuses on individual achievement, team science might differentially impact early stage researchers. The need to be recognized for individual accomplishments to move forward in an academic career may give rise to research team conflicts. Raising awareness to career-related aspects of team science will help individuals (particularly trainees and junior faculty) take steps to align their excitement and participation with the success of both the team and their personal career advancement.